Le relazioni adulto-bambino negli album fotografici di famiglia: un’esperienza di Public History per formare alle professioni educative - Bandini, Gianfranco; Caselli, Paola (Rivista Italiana di Educazione Familiare, 2019)
The paper illustrates a training experience – and its reasons – aimed at implementing professional skills of Early Childhood Education and Care pedagogical coordinators. The paper is based on the belief that historical knowledge can be a valid tool for understanding family relationships, and for effectively facing current educational challenges. In the general context of the history of the family, the reconstruction of the intergenerational passages of one’s family allows to reflect on the short and long-term dynamics that are still present today. Moreover, it promote the awareness of the variety of ethnic, religious, and identity components, which are part of daily work with children and their families. The training activity have been carried out promoting the use of family pictures, their digitalisation, and commentary, according to Public History.